At high dietary levels ethanol alters the structure of mid- and hindgut epithelial cells of Drosophila melanogaster larvae. - Hartman, J.R.; Dybas, L.K.; Geer, B.W. (Journal of Experimental Zoology, 1993)
The midgut of Drosophila melanogaster is a site of alcohol dehydrogenase (ADH) activity, the enzyme that catalyzes the first step in the major pathway for ethanol degradation. The effects of different levels of dietary ethanol on the ultrastructures of the guts of larvae of the Canton-S wild-type strain and the ADH-deficient, Adhn2, strain were ascertained. In wild-type larvae fed an ethanol-free, defined medium, the foregut epithelium was characterized by few glycogen rosettes and sparse microvilli that protruded into the gut's thick lumen lining. The midgut epithelium was typical of cells involved in absorption and active transport with abundant microvilli on the apical surface and membrane infoldings on the basal surface. In place of microvilli, the apical surface of the hindgut had membrane infoldings. The apical surfaces of both the mid- and hindgut epithelium were covered by a thick, electron-dense peritrophic membrane consisting of chitin. In both strains the subcellular damage that was correlated with ethanol levels in the diet was confined to the midgut and hindgut regions. Damage to gut cells in the form of disrupted mitochondria, dilated rough endoplasmic reticulum, low densities of glycogen rosettes and protein granules, high numbers of autophagic vacuoles, and the presence of myelin whirls was extensive in Canton-S strain larvae fed a high ethanol diet. A low dietary concentration of ethanol induced changes in gut ultrastructure of Adhn2 larvae similar to the changes that were observed in wild-type larvae fed the higher ethanol concentrations, but the basal infoldings were more dilated in the Adhn2 larvae. At high dietary concentrations the disruption of mid- and hindgut cells by ethanol appeared great enough to interfere with the digestion and absorption of nutrients.